Information Technologies and Mathematical Modelling 13th International Scientific Conference, ITMM 2014, named after A.F. Terpugov, Anzhero-Sudzhensk, Russia, November 20-22, 2014. Proceedings - Dudin, Alexander; Nazarov, Anatoly; Yakupov, Rafael; Gortsev, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 13th International Scientific Conference on Information Technologies and Mathematical Modeling, named after A.F. Terpugov, ITMM 2014, Anzhero-Sudzhensk, Russia, held in Anzhero-Sudzhensk, Russia, in November 2014. The 50 full papers included in this volume were carefully reviewed and selected from 254 submissions. The papers focus on probabilistic methods and models, queueing theory, telecommunication systems, and software engineering.
Probabilistic methods and models -- Queueing theory -- Telecommunication systems -- Software engineering.
Keywords: Computer science; Computer communication systems; Computer system failures; Mathematical statistics; Probabilities; Computer Science; Probability and Statistics in Computer Science; System Performance and Evaluation; Probability Theory and Stochastic Processes; Computer Communication Networks; Electronic books